Molecular interaction analysis and transport properties of binary liquid mixtures containing 1-Amino-2-propanol and alkyl acetates at T = 298.15–318.15 K: Application of Graph theory and DFT studies - Deepak Parmar; Manju Rani; Naveen Kumar; Noureddine ISSAOUI; Omar M. Al-Dossary; Kavitha Kumari; Mustapha Sahal; Leda G. Bousiakoug (Journal of Saudi Chemical Society, 2023)
The thermophysical properties of 1A2P (1-amino-2-propanol) (1) with AAc (methyl acetate (MAc) or ethyl acetate (EAc) or propyl acetate (PAc) or butyl acetate (BAc)) (2) were examined for understanding the molecular interactions between given binary liquid mixtures. Viscosity (η) was measured for 1A2P, AAc (alkyl acetate) and their binary mixture at five different temperatures (T = 298.15 to 318.15 K) and at 0.1 MPa pressure. From η data, the deviation in viscosity, Δη, and excess Gibbs free energy of activation, G∗E, were calculated. The Δη values were more positive for the 1A2P (1) + MAc (2) binary mixture at equimolar composition which indicate that there is strong intermolecular interaction between 1A2P and MAc molecules. Further, Δη values were also analyzed by Graph theoretical approach (GTA) and predicted that CO-----H-O interactions are stronger than OH----O-C interactions between 1A2P and AAc molecules in the liquid mixture which is also recognized by FTIR spectroscopic studies. Density functional theory (DFT) studies were employed to investigate the strength of molecular interactions.